2011
DOI: 10.1111/j.1551-2916.2011.04684.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of TiO2 Seed Layer Thickness on the Nanostructure Evolution and Phase Transformation Behavior of Sputtered PZT Thin Films During Post‐Deposition Air‐Annealing

Abstract: An optimum TiO2 seed layer is said to facilitate nucleation and subsequent growth of perovskite phase in Pb(Zr,Ti)O3 (PZT) films during annealing. The actual causes that prevent perovskite growth, particularly in sputtered PZT films on thick TiO2 seed layers are not yet understood clearly. Herein, based on the results of X‐ray diffractometry (XRD), field‐emission scanning electron microscopy (FESEM), and analytical scanning/transmission electron microscopy (S/TEM) with semi‐quantitative elemental mapping using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It has been previously shown that the preferred orientation of the PZT films can be maintained using relatively thick buffer layers [39]. Moreover, the thickness of the TiO 2 buffer layer between PZT and a substrate has been shown to be an important parameter to control the amount of diffused Pb into the substrate [40] as well as reducing leakage. Therefore, in the following experiments, in order to prevent the diffusion of Pb into GaN/Si during the PZT deposition, a 20 nm R-TiO 2 buffer layer was used.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that the preferred orientation of the PZT films can be maintained using relatively thick buffer layers [39]. Moreover, the thickness of the TiO 2 buffer layer between PZT and a substrate has been shown to be an important parameter to control the amount of diffused Pb into the substrate [40] as well as reducing leakage. Therefore, in the following experiments, in order to prevent the diffusion of Pb into GaN/Si during the PZT deposition, a 20 nm R-TiO 2 buffer layer was used.…”
Section: Resultsmentioning
confidence: 99%
“…roughness of the film surface is 13.11 nm and observed well-defined grain growth of PZT/ZnO structure. As can be seen from Figure 3(b), after nucleation, circular rosettes grow at right corner of the film along perpendicular direction to the substrate [15]. Figure 4(a) shows a typical C-V characteristic at room temperature for an Au/ZnO/Si (MIS) diode measured at 1 MHz with a small signal voltage of 200 mV, and the sweep rate of the bias voltage was 0.2 V/s.…”
Section: Resultsmentioning
confidence: 99%
“…The annealing process of titanium allows us to obtain a thin titanium dioxide film as the seed layer. This seed layer between PZT film and titanium substrate could not only prevent the formation of the pyrochlore/fluorite phase, but also improve the crystal quality of PZT films grown on lattice-incompatible substrates [28,29]. The process substrate was placed in a vacuum furnace, and air inside the furnace was drawn to reach a pressure of 20 mtorr.…”
Section: Fabrication Of Foil-based Microphone Transducermentioning
confidence: 99%